L = 2

L(L-1) = 2(L-1)

L2-L = 2L-2

L2-2L = L-2

L(L-2) = L-2

L = 1

Find the mistake in the above maths equations

L = 2

L(L-1) = 2(L-1)

L2-L = 2L-2

L2-2L = L-2

L(L-2) = L-2

L = 1

Find the mistake in the above maths equations

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestAccording to me 5th step is absolutely right but when you do the 2nd step you must mention l is not equal to 1 – Ashwin Upadhyay · 2 years, 3 months ago

Log in to reply

Fifth row, (L-2)=0 – Suradnyana Wisnawa · 3 years, 4 months ago

Log in to reply

– Suradnyana Wisnawa · 3 years, 4 months ago

I think the mistake is in the fifth row, where both side divided by (L-2) which is zeroLog in to reply

Fifth St ep is wrongg – Prasanna Krishna · 3 years ago

Log in to reply

Simple because of multiplying it by (L-1) it become quadratic ..So it has two solutions 1 & 2. – Aman Chaudhary · 3 years, 4 months ago

Log in to reply

Log in to reply

– Yashasvini Sharma · 3 years, 4 months ago

after 5th step do L^2-3L+2=0 and get L=2Log in to reply

2L-2 is 0 – Amey Sadegaonkar · 3 years, 4 months ago

Log in to reply

– Suradnyana Wisnawa · 3 years, 4 months ago

No, 2L-2 = 2Log in to reply

or 2 – Hany Shenouda · 3 years, 4 months ago

Log in to reply

fourth row. – Sajid Askari · 3 years, 4 months ago

Log in to reply

Fourth step equates zero to zero – Nikesh Neelakantan · 3 years, 4 months ago

Log in to reply